Altered Intracellular ATP Production by Activated CD4+ T-Cells in Very Preterm Infants. (13th December 2016) - Aquilano, Giulia; Capretti, Maria Grazia; Nanni, Francesca; Corvaglia, Luigi; Aceti, Arianna; Gabrielli, Liliana; Chiereghin, Angela; Faldella, Giacomo; Lazzarotto, Tiziana
Abstract : Background . The neonatal immune system is not fully developed at birth; newborns have adequate lymphocytes counts but these cells lack function. Objective . To assess the activity of T-cells and the influence of the main perinatal factors in very preterm infants (birth weight < 1500 g). Design . Blood samples from 59 preterm infants (21/59 were dizygotic twins) were collected at birth and at 30 days of life to measure CD4+ T-cell activity using the ImmuKnow™ assay. Fifteen healthy adults were included as a control group. Results . CD4+ T-cell activity was lower in VLBW infants compared with adults (p < 0.001 ). Twins showed lower immune activity compared to singletons (p = 0.005 ). Infants born vaginally showed higher CD4+ T-cell activity compared to those born by C-section (p = 0.031 ); infants born after prolonged Premature Rupture of Membranes (pPROM) showed higher CD4+ T-cell activity at birth (p = 0.002 ) compared to infants born without pPROM. Low CD4+ T-cell activity at birth is associated with necrotizing enterocolitis (NEC) in the first week of life (p = 0.049 ). Conclusions . Preterm infants show a lack in CD4+ T-cell activity at birth. Perinatal factors such as intrauterine inflammation, mode of delivery, and zygosity can influence the adaptive immune activation capacity at birth and can contribute to exposing these infants to serious complications such as NEC.